How do terrestrial wildlife communities respond to small‐scale Acacia plantations embedded in harvested tropical forest?. Issue 9 (20th September 2022) - Wong, Seth T.; Guharajan, Roshan; Petrus, Azrie; Jubili, Jaffly; Lietz, Robin; Abrams, Jesse F.; Hon, Jason; Alen, Lukmann H.; Ting, Nicholas T. K.; Wong, George T. N.; Tchin, Ling T.; Bijack, Nelson J. C.; et al.
Abstract: To offset the declining timber supply by shifting towards more sustainable forestry practices, industrial tree plantations are expanding in tropical production forests. The conversion of natural forests to tree plantation is generally associated with loss of biodiversity and shifts towards more generalist and disturbance tolerant communities, but effects of mixed‐landuse landscapes integrating natural and plantation forests remain little understood. Using camera traps, we surveyed the medium‐to‐large bodied terrestrial wildlife community across two mixed‐landuse forest management areas in Sarawak, Malaysia Borneo which include areas dedicated to logging of natural forests and adjacent planted Acacia forests. We analyzed data from a 25‐wildlife species community using a Bayesian community occupancy model to assess species richness and species‐specific occurrence responses to Acacia plantations at a broad scale, and to remote‐sensed local habitat conditions within the different forest landuse types. All species were estimated to occur in both landuse types, but species‐level percent area occupied and predicted average local species richness were slightly higher in the natural forest management areas compared to licensed planted forest management areas. Similarly, occupancy‐based species diversity profiles and defaunation indices for both a full community and only threatened and endemic species suggested the diversity and occurrence were slightly higher in the natural forest management areas. At the local scale, forest quality was the most prominent predictor of species occurrence. These associations with forest quality varied among species but were predominantly positive. Our results highlight the ability of a mixed‐landuse landscape with small‐scale Acacia plantations embedded in natural forests to retain terrestrial wildlife communities while providing an alternate source of timber. Nonetheless, there was a tendency towards reduced biodiversity in planted forests, which would likely be more pronounced in plantations that are larger or embedded in a less natural matrix. Abstract : Industrial tree plantations are expanding to offset declining timber supply by shifting towards more sustainable forestry practices and to meet global demand for timber products. Using camera traps, we surveyed the medium‐to‐large bodied terrestrial wildlife community across two mixed‐landuse forest management areas in Sarawak, Malaysia Borneo which include areas dedicated to logging of natural forests and adjacent planted Acacia forests. Our results highlight the ability of a mixed‐landuse landscape with small‐scale Acacia plantations embedded in natural forests to retain terrestrial wildlife communities while providing an alternate source of timber.